KOLABORASI PEMANGKU KEPENTIANGAN DALAM PENGEMBANGAN DAYA TARIK WISATA EDU-TOURISM RUMAH ATSIRI INDONESIA - Truli Nugroho; Alex Soares Thomas; Yeslinda Rupidara; Devi Oktavia Rina; Gabriella Charoline Violeta Toelle; Oktaviana br Ginting (Sekolah Tinggi Pariwisata Sahid Surakarta, 2022)
The discourse on collaboration has attracted the attention of researchers from various fields of science and backgrounds. As one of the potential sectors, tourism development is very dependent on the role of stakeholders involved in it. Stakeholder collaboration is ideal for small-scale to large-scale tourist destinations. The role of stakeholders can significantly affect the success of developing a destination. This study was conducted at Rumah Atsiri Indonesia, an Edu-tourism destination in Tawangmangu District. This study aims to answer the question, how is the collaboration of stakeholders in the development of RAI, and what factors are the obstacles in the collaboration of RAI development? The data collection in this study was conducted through observation, interviews, and secondary data analysis. The results of the study found that collaboration between the private sector and the government sector has been going well. However, the community as hosts has not been maximally involved in the development of RAI tourism.